Additional commentary on deception in statin research. Issue 12 (2nd December 2017) - Diamond, David M.; Ravnskov, Uffe
Abstract : Response to : Ferenci T. Absolute risk reduction may depend on the duration of the follow-up. Expert Rev Clin Pharmacol. 2017;10(12):1409–1410.